2013
DOI: 10.3109/13880209.2013.834365
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition and apoptosis of Ehrlich ascites carcinoma cells by the methanol extract ofEucalyptus camaldulensis

Abstract: Context: Eucalyptus camaldulensis Dehnh. (Myrtaceae) is a tall evergreen tree found commonly in Bangladesh. Its use in traditional folk medicine for the treatment of various health complications are well known. Objective: To explore the in vivo antitumor effect of Eucalyptus camaldulensis stem bark methanol extract (ME) against Ehrlich's ascites carcinoma (EAC) in Swiss albino mice. Materials and methods: The antitumor activity of ME was studied by determining viable tumor cell count, recording tumor weight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
4
28
0
Order By: Relevance
“…Eucalyptus camaldulensis stem bark methanol extract -treated EAC cells showed membrane blebbing, chromatin condensation, nuclear fragmentation (apoptotic features) in Hoechst 33342 staining under fluorescence microscope. The DNA profile in agarose gel (1.5%) electrophoresis also confirmed that Eucalyptus camaldulensis stem bark methanol extract caused EAC cell death by apoptosis [134].…”
Section: Cytotoxic Effectmentioning
confidence: 68%
“…Eucalyptus camaldulensis stem bark methanol extract -treated EAC cells showed membrane blebbing, chromatin condensation, nuclear fragmentation (apoptotic features) in Hoechst 33342 staining under fluorescence microscope. The DNA profile in agarose gel (1.5%) electrophoresis also confirmed that Eucalyptus camaldulensis stem bark methanol extract caused EAC cell death by apoptosis [134].…”
Section: Cytotoxic Effectmentioning
confidence: 68%
“…DNA fragmentation assay. DNA fragmentation assay by agarose gel electrophoresis was determined by the method described previously (Islam et al, 2014a). EAC cells were collected from mice treated with (five consecutive days at 2.0 mg/kg/day) and without the compound EC-1.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has previously reported that petroleum ether and methanol extracts of this plant exhibit promising anticancer activity against Ehrlich ascites carcinoma (EAC) cells in Swiss albino mice in a dose-dependent manner Islam et al, 2014a). These results inspired us to develop compound of natural origin with anticancer effect.…”
Section: Introductionmentioning
confidence: 99%
“…The safe daily oral dose in human adults is 300-600 mg, while semisolid preparations for topical use may contain 5-20% of Eucalyptus oil (Blumenthal and Busse, 1998;Tisserand and Young, 2014). Similarly, E. camaldulensis bark methanolic extract LD50 value for Swiss albino mice (Mus musculus) is very high -1120 mg/kg, indicating its low host toxic effects (Islam et al, 2014). The low toxicity and natural origin of E. camaldulensis essential oil and extracts, in contrast to synthetic antimicrobials, favor their application as antimicrobial agents.…”
Section: Eucalyptus Camaldulensis Traditional and Contemporary Applicmentioning
confidence: 99%
“…Crude methanol leaf extracts of E. camaldulensis from Iran had saponins, tannins, volatile oils, and balsam (gum), while the components such as anthraquinones, hydrolysable tannin, flavonoid, alkaloid, and glycosides were not detected (Jouki and Khazaei, 2010); crude methanolic leaves extract of E. camaldulensis from India contained anthraquinones, flavonoids, saponins, and terpenoids, while alkaloids, cardiac glycosides, and tannins were not detected (Singh and Thakur, 2016). Phytochemical screening of the crude stem barks methanol extract of E. camaldulensis from Bangladesh indicated presence of saponins, flavonoids, tannins, and also volatile oils, while anthraquinones, hydrolysable tannins, alkaloids, and glycosides were not present (Islam et al, 2014). The polyphenolic composition (flavonoids and phenolic acids and aldehydes) also was studied in the soluble fractions of the methanolic extracts of Eucalyptus camaldulensis originating from two Spain provinces, Huelva and Pontevedra: gallic, protocatechuic, vanillic and ellagic acids, and protocatechic aldehyde were identified, along with eriodictyol, quercetin, naringenin, vanillin, naringin, quercitrin, luteolin, and kaempferol (Cadahia et al, 1997).…”
Section: Eucalyptus Camaldulensis Extracts Chemical Compositionmentioning
confidence: 99%